2006
DOI: 10.1007/s10964-006-9070-5
|View full text |Cite
|
Sign up to set email alerts
|

Structure and validity of people in my life: A self-report measure of attachment in late childhood

Abstract: No self-report measure of attachment is well validated for middle-childhood. This study examined the validity and factor structure of the People in My Life (PIML) measure in 320 urban, fifth and sixth graders. Validity analyses consisted of correlational analyses between PIML subscales and the Child Behavior Checklist, Delinquency Rating Scale for Self and Others, Heath Resources Inventory, and Reynolds Child Depression Scale. Validity correlations were consistent with a-priori hypotheses. Confirmatory factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 70 publications
(68 reference statements)
7
93
0
5
Order By: Relevance
“…In the present sample, the instrument revealed good internal consistency with Cronbach's alphas of .83 (mothers) and .85 (fathers). Ridenour et al 2006) was used to assess the children's and adolescents' representations of the relationships with their parents, and therefore, the extent to which the parents are perceived as secure attachment figures. This scale includes three subscales: (1) Trust, which assesses the degree of mutual respect and trust in the relationship (e.g., "My parents respect my feelings"); (2) Communication, which assesses the quality of verbal communication with parents (e.g., "I talk to my parents when I am having a problem"); and (3) Alienation, which assesses negative affective-cognitive experiences in the relationship with parents, such as feelings of anger, isolation, and alienation (e.g., "I feel angry with my parents").…”
Section: Methodsmentioning
confidence: 99%
“…In the present sample, the instrument revealed good internal consistency with Cronbach's alphas of .83 (mothers) and .85 (fathers). Ridenour et al 2006) was used to assess the children's and adolescents' representations of the relationships with their parents, and therefore, the extent to which the parents are perceived as secure attachment figures. This scale includes three subscales: (1) Trust, which assesses the degree of mutual respect and trust in the relationship (e.g., "My parents respect my feelings"); (2) Communication, which assesses the quality of verbal communication with parents (e.g., "I talk to my parents when I am having a problem"); and (3) Alienation, which assesses negative affective-cognitive experiences in the relationship with parents, such as feelings of anger, isolation, and alienation (e.g., "I feel angry with my parents").…”
Section: Methodsmentioning
confidence: 99%
“…While gender differences on general peer attachment as well as on trust and communication seemed to be well established, differences on alienation are less consistent (e.g., Nada Raja et al 1992;Ruijten et al 2011;Song et al 2009). In particular, some studies reported that males were more alienated than females (Gullone and Robinson 2005;Lapsley et al 1990;Pace et al 2011) while most studies reported no significant gender differences (e.g., Guarnieri et al 2010;Muris et al 2001;Nada Raja et al 1992;Nickerson and Nagle 2004;Noppe and Noppe 1997;Ridenour et al 2006;Ruijten et al 2011;San Martini et al 2009), with few studies reporting that females were more alienated than males (e.g., Song et al 2009). In this study, we used a meta-analytic approach to synthesize literature on gender differences and to test which moderators could explain variations in the effects reported in previous studies.…”
Section: Gender Differences On Peer Attachmentmentioning
confidence: 99%
“…Confidence in maternal support was estimated with the Trust-subscale of the People In My Life Questionnaire which is designed to measure 10 to 12-year-old children's representations of attachment figures (PIML, Ridenour, Greenberg, & Cook, 2006). This questionnaire is a child-friendly version of the Inventory of Parent and Peer Attachment (Armsden & Greenberg, 1985), which assesses Trust in the attachment figures' support, Communication about distress, and Alienation from the attachment figure (e.g., Allen, Porter, MacFarland, et al, 2007;Belsky, Jaffee, Hsieh, & Silva, 2001).…”
Section: Attachment-related Expectationsmentioning
confidence: 99%